THE POTENTIAL OF PENICILLIUM CITRINUM AND PENICILLIUM OXALICUM IN THE FORMATION OF SUPRESSIVE SOIL AGAINST FUSARIUM WILT BANANA WITH METAGENOMICS BASED CO OCCURRENCE MODEL - Margareta, Alfriana
Fusarium wilt disease caused by the pathogenic fungus Fusarium oxysporum f.sp. cubense (Foc) is a serious threat to banana production in Indonesia. Foc infection has been detected in all regions of Aceh to Papua and has eliminated thousands of hectares of public and private banana plantations. Conventional control of fusarium wilt such as fumigation, fungicides and development of resistant banana cultivars against Foc is still less effective. Another strategy that is more effective is the use of fungus which have potential to induce suppressive soil formation based on the omics approach (metagenomic, transcriptomic, proteomic, etc). Suppressive soil plays a role in suppressing the development of pathogens in the soil rhizosphere. Therefore, a research aimed at obtaining potential fungi in suppressive soil formation was carried out through community structure analysis and the ITS2 metagenomic based on co-occurrence model. Two suppressive soil samples and two conducive soil samples were taken from banana plantation PTPN VIII Sukabumi. DNA isolation was carried out using a ZymoBIOMICS™ DNA Miniprep Kit and then sequenced using Illumina HiSeq. The results of the sequencing data were analyzed using quality control (FASTQC ver.0.11.5) which has a sequence Phred score above 30. Further bioinformatics analysis uses several software, namely QIIME2 as the main pipeline with the UNITE, R and Gephi taxonomic databases for co-occurrence network patterns model. Suppressive soil samples showed the highest diversity value based on the alpha diversity index, while the beta diversity tested by PcoA showed the formation of clusters among suppressive soil samples, but not in conducive soils. The fungi group through comparative analysis of abundance at the genus level in suppressive soil was dominated by Penicillium and in conducive soil was dominated by Rigidoporus. The fungi group through comparative analysis of abundance at the species level showed that P. citrinum and P. oxalicum was relatively higher in suppressive soils compared to conducive soils which were dominated by Rigidiporus ulmarius and Fusarium oxysporum. The co-occurrence network pattern on the suppressive soil has a higher number of positive interactions than the conducive soil with varying species degree values. Meanwhile, in the co-occurrence network model, infected soil has the same degree value. P. citrinum and P. oxalicum have a degree value of 16, the highest for positive interactions co-occurrence in suppressive soils. Based on the results of this study, P. citrinum and P. oxalicum have the potential to form suppressive soils, the mechanism of which is unknown and needs further study.